Education and modernization in the third world: the experience of Egypt - Hasan Langgulung (Universiti Kebangsaan Malaysia, 1980)
This paper was meant to investigate the role of education in enhancing political modernization in the Third World with a special reference to Egypt. Four functions of the political system which have a fairly clear relationship to education were the main concern, namely national integration, political participation, economic and social role of university graduates and the circulation of the ruling elite.